Malay version of the mhealth app usability Questionnaire (M-MAUQ): translation, adaptation, and validation study - Mustafa, Norashikin; Safii, Nik Shanita; Jaffar, Aida; Sani, Nor Samsiah; Mohamad, Mohd Izham; Abd Rahman, Abdul Hadi; Mohd Sidik, Sherina (JMIR Publications Inc., 2021)
Background: Mobile health (mHealth) apps play an important role in delivering education, providing advice on treatment, and monitoring patients’ health. Good usability of mHealth apps is essential to achieve the objectives of mHealth apps efficiently. To date, there are questionnaires available to assess the general system usability but not explicitly tailored to precisely assess the usability of mHealth apps. Hence, the mHealth App Usability Questionnaire (MAUQ) was developed with 4 versions according to the type of app (interactive or standalone) and according to the target user (patient or provider). Standalone MAUQ for patients comprises 3 subscales, which are ease of use, interface and satisfaction, and usefulness.